Health Science: Medical Treatment In Prophet’s Behaviour Context / Sains Kesihatan: Perubatan Dalam Konteks Tasarrufat Nabawiyyah (Sains Humanika, 2020)
This article discusses the characteristics of speeches that come from Prophet Muhammad (PBUH) on his medical prophetic. It aims to clarify Taṣarrufāt Nabawiyyah of the Prophet (PBUH) through authentic ahadeeth on medical issues. The diversity of roles of the Prophet (PBUH) has prompted variences between the the jusrists in the determination of legal opinion. There are several regarding the roles of the Prophet, for instance the role of being a guider, a mufti, a jurist, a leader and a human being. The consequence of that diversity, Islamic jurists have been arguing with each other to affirm the Syariah ruling on medical issues that came from the Prophetic medical traditions. The qualitative method was used to gather data and information that were consequently analysed. At the completion of the study, it was discovered that Taṣarrufāt Nabawiyyah could be one of the factors causing the misunderstanding of authentic ahadeeth on medical issues and thus this is the main reason for the need to understand the legal texts in accordance with Syariah purposes.
Keywords: Taṣarrufāt Nabawiyyah; authentic hadeeth; medical issues; shariah purposes; Islamic jurists